Two nanoscale self-assembling biomorphic systems: SiO2 nanorings and SiO2-carbonate crystals; 2nd International Symposium on Nanoscience and Nanomaterials SINN, Ensenada, Baja California, Mexico, March 4-8, 2012, CNyN-UNAM, "Welcome to the Bionanotechnology Group" - Moreno A.; Martynyuk O. A. Oksana Anatolievna; Bogdanchikova N.; Ruiz F.; Zepeda T.; Avalos M. B.; Pestryakov A. N. Aleksey Nikolaevich; Luna R. V. G.; Huerta-Saquero A. (2013, 2013)
В фонде НТБ ТПУ отсутствует